The impacts of early marriage on young women in Indonesia - Kusuma Wardani, Indah (BKM Public Health and Community Medicine, 2021)
Objective: This paper reviews information about the impacts of early marriage on the health of young women in Indonesia. Content: Early marriage can affect the high rate of maternal mortality, infant mortality and will affect the low level of health of mothers and children. Early marriages often occur in communities experiencing economic difficulties. Due to financial difficulties for continuing education, parents are forced to marry off their children at an early age. The community is still less aware of the dangers posed by early marriage, besides that the beliefs and customs that apply in the community also determine the occurrence of early marriage. One of the developing cultures in Indonesia is that if a girl gets married over the age of 20, she will become an old maid and will be a disgrace to her family. The physiological impact of early marriage is miscarriage, premature labor, low birth weight, congenital abnormalities, easy infection, anemia and even maternal death. Meanwhile, the psychological impact is the feeling of regret after marriage so that there are frequent quarrels and arguments in the household. Domestic violence in early childhood couples can lead to divorce.